PENGARUH FAKTOR DEMOGRAFI DAN KELAS SOSIAL TERHADAP KEPUTUSAN NASABAH MEMILIH BANK SYARIAH DI KOTA PALOPO - Zainuddin, Raehana (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2019)
This thesis discusses about the influence of demographic and social class factors on the customer's decision to choose Islamic (Syariah) banks in Palopo, this research purpose to prove the demographic factors and social classes that influence the customer's decision to choose Islamic (Syariah) banks in Palopo and prove the influence of these factors simultaneously. To provide answers to the problems stated above, the writer uses a quantitative research approach with the variables used in this research were independent variables namely education, income, employment, dependents and age and the dependent variable in the form of customer decisions to choose Islamic (Syariah) banks. This research took as many as 100 respondents with the Non Probability Sampling method as sampling. Data collection in this research uses a questionnaire with regression analysis techniques through the F test and t test using Statistical Product and Service Solutions (SPSS) Software 19.0. The results of this research showed that education, income, employment, and age had a significant effect on the customer's decision to choose Islamic (syariah) banks in Palopo. This was proven by obtaining a significance value of 0,000 or less than 5% (0.05). The results of the partial statistical test also show that the variables of education, income, employment, have a significant positive effect while the age variable has a significant negative effect on the customer's decision to choose Islamic banks in Palopo. Based on the beta coefficient of regression, the largest coefficient value was the income variable of 7,060 with a significance level of 0,000. this finding shows that income was the variable that most influences the customer's decision to choose a Syariah Bank among four other variables. Based on the results of the simultaneous test, it was concluded that simultaneous independent variables represented by the variables of education, income, employment, dependents and age had a significant effect on the variables bound by customer decisions